Adelard of Bath: Original Works and Translations - Alowais, Aisha; Idriz, Mesut (Al-Adab Journal, 2021)
In the 12th century, a large number of European scholars have travelled to the East in order to learn and ultimately bring back with them new scientific knowledge. Translators played the major role. Among those translators is Adelard of Bath whom this study aims to investigate his original works along with the works he translated from Arabic into Latin. The study will follow his travels from his hometown of Bath to France where he studied, and finally to the East where he learned from the Arabs. It will also briefly highlight the situation of education during the so-called Dark Ages in Europe. Moreover, Adelard’s original works before and after travelling are examined in order to see to what extent Adelard was influenced by the Arabs. Adelard’s translated books into English are used as primary resources for this research, in addition to other secondary references. As a result of conducting this research, it can be seen that the thought of Arabs have prevailed in Adelard’s works as he stressed the importance of the methodology followed by them. Adelard has contributed to forming a cusp between the Islamic Civilization and the European Renaissance; and hence further studies need to be carried out about Adelard as well as his endeavors with East.